In-hospital prescription changes and documentation in the medical records of the primary care provider: results from a medical record review study - Judith M. Poldervaart; Marije A. van Melle; Sanne Willemse; Niek J. de Wit; Dorien L.M. Zwart (BMC, 2017)
Abstract Background An increasing number of transitions due to substitution of care of more complex patients urges insight in and improvement of transitional medication safety. While lack of documentation of prescription changes and/or lack of information exchange between settings likely cause adverse drug events, frequency of occurrence of these causes is not clear. Therefore, we aimed at determining the frequency of in-hospital patients' prescription changes that are not or incorrectly documented in their primary care provider's (PCP) medical record. Methods A medical record review study was performed in a database linking patients' medical records of hospital and PCP. A random sample (n = 600) was drawn from all 1399 patients who were registered at a participating primary care practice as well as the gastroenterology or cardiology department in 2013 of the University Medical Center Utrecht, the Netherlands. Outcomes were the number of in-hospital prescription changes that was not or incorrectly documented in the medical record of the PCP, and timeliness of documentation. Results Records of 390 patients included one or more primary-secondary care transitions; in total we identified 1511 transitions. During these transitions, 408 in-hospital prescription changes were made, of which 31% was not or incorrectly documented in the medical record of the PCP within the next 3 months. In case changes were documented, the median number of days between hospital visit and documentation was 3 (IQR 0-18). Conclusions One third of in-hospital prescription changes was not or incorrectly documented in the PCP's record, which likely puts patients at risk of adverse drug events after hospital visits. Such flawed reliability of a routine care process is unacceptable and warrants improvement and close monitoring.